Biomedical cellular imaging using digital holographic photothermal microscope - Hendry Renaldo. (2011)
Biomedical imaging is one of the most essential tools in the medical world today. It is the main application utilized for providing early and accurate information about abnormalities occurring in the body leading to cancer and other diseases. The current available imaging modalities up till today nevertheless, has yet to provide a decent method of imaging at the cellular and organelle level where diseases or cancer may arise.